Language change and linguistic theory . Vol. 1, Approaches, methodology and sound change - Miller, D. Gary (Oxford Linguistics, 2010)
This two volume work examines every aspect of language change and two centuries of linguistic approaches towards understanding it. In its comprehensive approach and great linguistic and historical range, this is a contribution of enduring use and value to historical linguistics and linguistic theory.